"Geranium biuncinatum" (Geraniaceae): new record for the flora of Iran - Esfandani-Bozchaloyi, Somayeh; Attar, Farideh (Mediterranean Botany, 2018)
Geranium biuncinatum Kokwaro was collected during a fieldwork around (Khuzestan province, Shoshtar to Masjed Soleyman) in South West of Iran. It is added as a new record for the flora of Iran. Micromorphological features of mericarps and seeds are investigated by Scanning Electron Microscopy. Differences between Geranium biuncinatum and its relatives are discussed. Its diagnostic characters, geographical distribution map and detailed pictures are given.